Pro-inflammatory diet and risk of prostate diseases, lower urinary tract symptoms: A cross-sectional study from the National Health and Nutrition Examination Survey (NHANES) 2003 to 2008 - Yang, Zhengping; He, Jibao; Hong, Anjie; Zhang, Li; Zhao, Haoyu; Wei, Chongrui; Niu, XueYan; Zhang, Zhijie (Medicine (Baltimore), 2024)
Evidence suggests a strong association between prostate diseases, lower urinary tract symptoms (LUTS), and pro-inflammatory diets. Our study was conducted to assess the relationship between the Dietary Inflammatory Index (DII) and prostate diseases, LUTS using the 2003 to 2008 U.S. National Health and Nutrition Examination Survey (NHANES) database. After the chi-square test to investigate whether demographic data and prostate diseases, LUTS were correlated, for positive results, we performed weighted multivariable logistic regression models analysis. In addition, we performed nonlinear tests using restricted cubic spline (RCS) and assessed the stability between different subgroups by subgroup and interaction analyses. The study included 30,619 subjects. After adjusting the regression model for fully confounding variables, DII was only correlated with benign prostatic hyperplasia (BPH) (OR = 1.074, 95% CI = 1.016-1.136; P = .012). And, the RCS relationship between DII and BPH was positively correlated (nonlinear: P = .830). We did not find statistically significant interactions in all subgroups. At the same time, we did not find any correlation between DII and other prostate diseases and LUTS. Pro-inflammatory diets are associated with an increased risk of BPH. Dietary modifications to reduce the intake of pro-inflammatory nutrients can be helpful in mitigating the development of BPH.